Impact of COVID-19 pandemic measures on hospitalizations and epidemiological patterns of twelve respiratory pathogens in children with acute respiratory infections in southern China - Wei Wang; Xiaojuan Luo; Zhenmin Ren; Xiaoying Fu; Yunsheng Chen; WenJian Wang; Yanmin Bao; Yuejie Zheng; Ke Cao; Jiehua Chen (BMC Infectious Diseases)
Abstract Objectives To investigate the impact of COVID-19 pandemic measures on hospitalizations and the alterations and persistence of the epidemiological patterns of 12 common respiratory pathogens in children during the COVID-19 pandemic and after the cessation of the “zero-COVID-19” policy in southern China. Methods Respiratory specimens were collected from hospitalized children with acute respiratory infections at Shenzhen Children’s Hospital from January 2020 to June 2024. Twelve common respiratory pathogens were detected using multiplex PCR. Data on demographic characteristics, pathogen detection rates, epidemiological patterns, co-infections, and ICU admission rates were compared between the ‘during COVID-19’ period (Phase 1: January 2020 to December 2022) and the ‘post COVID-19’ period (Phase 2: January 2023 to June 2024). Results In Phase 2, there was a significant increase in average annual cases, with a higher median age of affected children, higher pathogen detection rates, and increased co-infection rates compared to Phase 1. The epidemiological patterns of most pathogens were altered by the COVID-19 pandemic. Human Parainfluenza Virus, Human Metapneumovirus, Human Bocavirus (HBOV), and Human Coronavirus remained active during Phase 1, while Mycoplasma pneumoniae (Mp) and Adenovirus (ADV) were low, and Respiratory Syncytial Virus (RSV) lacked a seasonal peak in 2022. In Phase 2, Mp, ADV, and RSV experienced outbreaks, with Mp’s high prevalence continuing into 2024. RSV showed out-of-season epidemics for two consecutive years. Influenza A (H1N1), Influenza A (H3N2), and InfB lost their seasonal patterns during Phase 1 but reemerged and regained their seasonal characteristics in 2023–2024. ICU admission rates did not significantly differ between the two phases, except for HBOV, which had higher rates in Phase 2. Conclusion The epidemiological patterns of various respiratory pathogens were affected by the COVID-19 pandemic to varying degrees. Pathogens suppressed during the pandemic experienced outbreaks or out-of-season epidemics after the lifting of non-pharmaceutical interventions, with Mp and RSV continuing into the second year and HBOV associated ICU admission rates increasing in the post-pandemic era. Continuous monitoring of these patterns is essential to understand the duration of these effects and to inform effective response strategies.